Assessment of the geomorphic indices in relation to tectonics along selected sectors of Borpani River Basin, Assam using Cartosat DEM data - Shabnam Makrari; Gopal Sharma; Ajay Kumar Taloor; M. Somorjit Singh; K.K. Sarma; S.P. Aggarwal (Geosystems and Geoenvironment, 2022)
We studied geomorphic indices related to tectonics along the Borpani River using Cartosat 10 m spatial resolution Digital Elevation Model (DEM) data. A total of 11 geomorphic indices such as transverse topographic symmetry factor (Tt), drainage basin asymmetry (AF), valley floor width to valley height ratio (Vf), bifurcation ratio (Rb), hypsometric integral (HI), basin elongation ratio (Re), basin shape index (Bs), circularity ratio (Rc), drainage density (Dd), relief ratio (Rh), hypsometric curves (HC) were studied to access the tectonics along the river in selected locations. Five locations along the river were selected for detailed analysis (sub-basin I, II a, II b, III, and IV). Horton's (1945) scheme was adopted for watershed delineation, while stream ordering was performed using Strahler's (1964) method. The results infer that the sub-basins along the Borpani River are tectonically active. In the case of sub-basin I, 3 geomorphic indices out of 11 falls in the category of highly active, and 2, 1, 2, and 4 indices out of 11 falls in the category of highly active in the case of sub-basins II a, II b, III, and IV. Similarly, 4, 1, 3, 6, 1 and 4, 8, 7, 3, 6 indices fall under moderately active and low active classes in sub-basins I, II a, II b, III, and IV. On average, 23.86 %, 29.54%, and 46.58% of the geomorphic indices fall in the active, moderately active, and low active classes.